Determination of exterior convective heat transfer coefficient for low-rise residential buildings. Issue 5 (3rd September 2021) - Lu, Xinrui; Memari, Ali M.
ABSTRACT: This study is focused on the determination of exterior convective heat transfer coefficient for low-rise residential buildings. The convective heat transfer coefficient is an important parameter in building heat transfer analysis and building energy simulation. While there are many open literature studies based on either laboratory measurement or field testing, researchers have used different sources of wind data, testing conditions and building types, and therefore an applicable correlation especially for low-rise residential buildings is somewhat missing. In this study, a new calculation model is applied that comprehensively considers the influence of sky temperature, ground temperature as well as view factors. Several correlations are developed for both the convective heat transfer coefficient and the ground temperature, and an appropriate sky temperature model is selected. Based on the test data, an ASHRAE formula is also used to estimate the local wind speed using the free stream wind speed. The results of this study will provide new correlations of the convective heat transfer coefficient that can be used for low-rise residential buildings in the energy simulation process.